2021
DOI: 10.17932/ejoss.2021.023/ejoss_v02i1002
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Organizational Citizenship Behavior and Job Satisfaction among Physiotherapists of Hospitals of Karachi, Pakistan

Abstract: This study measured the relationship between organizational citizenship behavior and job satisfaction among physiotherapists located in Karachi hospitals of Pakistan. Further investigated how the variables affected by gender and educational status of physiotherapists. The survey was conducted to collect the data from respondents by adopting the tools of JSS and OCB-checklist. SPSS 21.0 was used for analyzing the data. Pearson correlation and independent sample t-test were applied for association and comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…The teachers reported feeling overworked, which led to stress and burnout, resulting in decreased performance in classroom. Additionally, study by Ali et al (2021) found that workload was negatively linked with teacher job satisfaction in public sector universities in Pakistan. Haroon and Uzma (2019) conducted in Lahore, Pakistan, found that high workload was associated with the decrease in student's academic achievement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The teachers reported feeling overworked, which led to stress and burnout, resulting in decreased performance in classroom. Additionally, study by Ali et al (2021) found that workload was negatively linked with teacher job satisfaction in public sector universities in Pakistan. Haroon and Uzma (2019) conducted in Lahore, Pakistan, found that high workload was associated with the decrease in student's academic achievement.…”
Section: Literature Reviewmentioning
confidence: 99%